Chronic exposure to mono-(2-ethylhexyl)-phthalate causes endocrine disruption and reproductive dysfunction in zebrafish - Zhu, Yongtong; Hua, Rui; Zhou, Yao; Li, Hong; Quan, Song; Yu, Yanhong (Environmental toxicology and chemistry, 2016)
Phthalic acid esters are frequently detected in aquatic environments. In the present study, zebrafish were exposed to low concentrations (0 µg/L, 0.46 µg/L, 4.0 µg/L, and 37.5 µg/L) of mono‐(2‐ethylhexyl) phthalate (MEHP) for 81 d, and the effects on reproduction, gamete quality, plasma vitellogenin (VTG), sex steroids, and transcriptional profiles of key genes involved in steroidogenesis were investigated. The results demonstrated that egg production and sperm quality were decreased after exposure to MEHP, which also resulted in reduced egg diameter and eggshell as well as decreased egg protein content. Significant inductions in plasma testosterone and 17β‐estradiol (E2) were observed in females, which might have resulted from up‐regulation of CYP19a and 17β‐HSD gene transcription in the ovary. A significant increase in plasma E2 along with a decrease in plasma 11‐keto testosterone was also observed in males, which was accompanied by up‐regulation of CYP19a and inhibition of CYP11b transcription in the testis. In addition, plasma vitellogenin levels were significantly increased after MEHP exposure in both sexes. Moreover, continuous MEHP exposure in the F1 embryos resulted in worse hatching rates and increased malformation rates compared with embryos without MEHP exposure. Taken together, these results demonstrate that MEHP has the potential to cause reproductive dysfunction and impair the development of offspring. However, it should be noted that most of the significant effects were observed at higher concentrations, and MEHP at typically measured concentrations may not have major effects on fish reproduction and development. Environ Toxicol Chem 2016;35:2117–2124. © 2016 SETAC